Motion control system simulation of cylindrical linear induction motor used in circuit breaker operating mechanism - Liu Ai-min; Li Jia-jue; Li Yong-xiang; Lin Xin (2009 IEEE International Conference on Automation and Logistics, 2009)
According to the requirements of movement characteristics during the opening and closing of 40.5 kV vacuum circuit breaker on operating mechanism, this paper designed a new type of motor drive operating mechanism-cylinder linear induction motor (C-LIM) drive mechanism. Based on the characteristics of short trip, strong anti-force, high speed in mechanism, analysis of the motor mechanism movement characteristics calculated the dynamic characteristics of the contact under the optimized velocity curve and also plan the move curve of the contact in the paper. Pointing at proper border effect of C-LIM mathematical model is built of vector control system when consider dynamic vertical border effect, and simulated of the mechanism control system for driven by (C-LIM) in MATLAB environment. The simulation results show that it can get a good dynamic performance, small vibration and perfectly meet the requirements of mechanism movement characteristics during the opening and closing of circuit breaker when the linear motor direct drive circuit breaker actuator operating shaft, and still lay the foundations of circuit breaker intelligence control.